1994
DOI: 10.1017/s0031182000080641
|View full text |Cite
|
Sign up to set email alerts
|

Continuous cultivation of intraerythrocytic Plasmodium falciparum in a serum-free medium with the use of a growth-promoting factor

Abstract: Serum-free media were used to culture Plasmodium falciparum. A commercial preparation, Daigo's GF21 developed as a growth-promoting factor for many kinds of mammalian cells, and consisting of the 55-70% ammonium sulphate fraction of adult bovine serum, insulin, transferrin, ethanolamine and sodium selenite, was found to sustain growth of the parasite when Daigo's T was employed as a basal medium. The optimal Daigo's GF21 concentration for parasite growth was between 5 and 20% (v/v), with the best results at 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 11 publications
1
43
0
Order By: Relevance
“…1982;Lingnau et al, 1994;Mi-Ichi et al, 2006;Nivet et al, 1983;Ofulla et al, 1993;Willet and Canfield, 1984), the establishment of a fully-defined culture medium for the parasite has represented a major challenge. We previously reported that GFS supported intraerythrocytic growth of P. falciparum (Asahi and Kanazawa, 1994;Asahi et. al., 1996;Asahi et al, 2005).…”
Section: Cdm For Continuous Intraerythrocytic Growth Of P Falciparummentioning
confidence: 93%
See 3 more Smart Citations
“…1982;Lingnau et al, 1994;Mi-Ichi et al, 2006;Nivet et al, 1983;Ofulla et al, 1993;Willet and Canfield, 1984), the establishment of a fully-defined culture medium for the parasite has represented a major challenge. We previously reported that GFS supported intraerythrocytic growth of P. falciparum (Asahi and Kanazawa, 1994;Asahi et. al., 1996;Asahi et al, 2005).…”
Section: Cdm For Continuous Intraerythrocytic Growth Of P Falciparummentioning
confidence: 93%
“…The parasites were routinely maintained using in vitro culture techniques. The culture medium was devoid of whole serum, and consisted of basal medium supplemented with 10% GFS (Daigo's GF21; Wako Pure Chemical Industries, Japan), as previously reported (Asahi, 2009;Asahi & Kanazawa, 1994;Asahi et al, 1996;Asahi et al, 2005;Asahi et al, 2011). This complete medium is referred to as GFSRPMI.…”
Section: Parasites and Culturementioning
confidence: 99%
See 2 more Smart Citations
“…To avoid the obstacles associated with the dependence on human serum, including unpredictable risks with infectious agents and difficulties in securing normal human sera, particularly in malaria endemic areas, and in obtaining a particular blood group, human serum substitutes such as a growth-promoting fraction derived from adult bovine plasma (GFS; Wako Pure Chemical Industries Ltd., Japan) and lipid-enriched bovine albumin (AlbuMAX I; Life Technologies, Japan) have been exploited success-fully [4,5], and have been employed widely for in vitro cultivation of P. falciparum. However, sufficient information on the constituents of the serum substitutes is still lacking.…”
Section: Introductionmentioning
confidence: 99%